A Low-Carbon Smart Campus Created by the Strategic Usage of Space—A Case Study of Korea University - Da Yeon Park; Mi Jeong Kim (Buildings, 2025)
In the context of the building sector, university campus buildings play a crucial role in promoting a green economic transition toward carbon neutrality, as universities are among the largest emitters of greenhouse gases. This research proposed a strategy for the operation and management of university campuses that focused on reducing energy consumption by optimizing the utilization of building spaces. To gather empirical data, a case study was conducted to examine the energy consumption of campus buildings based on their characteristics at Korea University. The results indicated that effective space utilization, achieved through the efforts of stakeholders, led to a reduction in heating and cooling energy consumption. To achieve this, the study classified university buildings by considering both physical variables and human-centered factors that affect energy consumption, analyzed space usage behavior, and compared heating and cooling energy consumption across buildings. This study expands current knowledge because its approach differs from previous research, which has generally focused on using simulation tools to analyze factors associated with the physical aspects of buildings—such as the energy performance of a building envelope or the energy-efficiency of facility systems.